Alcohol consumption and the risk of incident pulmonary embolism in US women and men. (12th August 2018) - Harrington, L. B.; Hagan, K. A.; Mukamal, K. J.; Kang, J. H.; Kim, J.; Crous‐Bou, M.; Lindström, S.; Rimm, E. B.; Kabrhel, C.; Jensen, M. K.
Abstract : Essentials The association of moderate alcohol consumption with pulmonary embolism (PE) risk remains unclear. In three large US cohorts, we evaluated the association of alcohol consumption with PE risk. We found no evidence of an association of alcohol consumption amount or frequency with PE risk. Secondary analyses of type and heavy episodic drinking also yielded null findings. Summary: Background: Moderate alcohol consumption has been variably associated with hemostatic and fibrinolytic factor levels, but the association between alcohol consumption and the risk of incident pulmonary embolism (PE) remains uncertain. Objective: To evaluate alcohol consumption amount and frequency in relation to PE risk. Methods: Nurses' Health Study (NHS), NHS II and Health Professionals Follow‐Up Study participants free of venous thromboembolism (VTE) at baseline ( n = 217 442) reported alcohol consumption by type, quantity and frequency, every 2–4 years. Incident PE cases were identified by self‐report and confirmed for participants without cancer. In this cohort study, we used Cox proportional hazards models to estimate multivariable‐adjusted hazard ratios (HRs) for PE associated with alcohol consumption amount and, separately, frequency. Secondary analyses evaluated alcohol type and heavy episodic drinking in relation to PE risk, and amount and frequency in relation to medical record‐confirmed idiopathic PE and any self‐reported VTE risk. Cohort‐specific analyses were pooled using random‐effects meta‐analysis. Results: During ≥ 20 years of follow‐up, we identified 1939 PE events. We found no strong evidence of an association between PE risk and alcohol consumption amount (pooled HRadj for 5.0–14.9 g day −1 vs. abstention = 0.97 [95% CI, 0.79, 1.20]) or frequency (pooled HRadj for 5–7 drinking days per week vs. abstention = 1.04 [95% CI, 0.88, 1.23]). Secondary analyses of type, heavy episodic drinking, idiopathic PE and VTE also yielded null findings. Conclusions: Among three large prospective cohorts of US men and women, we found no evidence of an association between the amount or frequency of alcohol consumption and PE risk.